On the future of the European Union: Normative derivation and restructuring potential in the new Multiannual Financial Framework - Berthold Busch; Jürgen Matthes (Institut der deutschen Wirtschaft (IW), 2018)
The debate concerning the future of the EU has been in full swing ever since Emmanuel Macron's (2017) Sorbonne speech. New threats to internal and external security in Europe require a stronger EU. In addition, Brexit is ripping a hole in the EU finances. This pressure for reform must be used to establish new priorities in the EU budget when discussions are held about the next Multiannual Financial Framework (MFF) 2021-2027. The European Commission has put forward different options for consideration as part of the discussion process, and this study is based on them. It takes the form of a normative review of EU tasks, which has two evaluation criteria: Firstly, there will be a discussion concerning which political areas should be the responsibility of the EU, and which of the member states. Cross-border spillover effects, economies of scale, preference differences and the subsidiarity principle, all have an important role to play when assessing EU added value on the basis of existing criteria and studies. Secondly, various policy fields will be examined to establish whether, and to what extent, they meet Musgrave's three criteria of public finance policy: allocation/growth, distribution/structural change cushioning, macro-economic stabilisation. [...]
Keywords: H61; O52; H41; 330